The Other Side of the Hill and Home Again - Hart, B. H. Liddell (London Cassel and Company Ltd., 1951)
In the PAN GRAND STRATEGY series, this is an account of Germany's generals, including their own version of the military events of 1939-1945 and details of their rise and fall, presenting a picture of the Second World War as it was seen by the men who commanded the panzer divisions and the might of the Wehrmacht. Originally published in 1948.
Includes Maps and Index
Keywords: World War, 1939-1945 -- Campaigns -- Generals -- Germany